El dribling del fútbol y la rapidez de movimiento en jóvenes - Pacheco Quezada, Flavio Gabriel (2025)
The main objective of this research was to improve the teaching and development of soccer dribbling through the speed of movement in young people. Theoretically, it was possible to identify dribbling as the technical action that allows the ball to advance or progress on the field of play, maintaining control or possession and outflanking the opponent so that they do not intervene in the game. It is also known that speed can be a quality that determines an athlete's motor performance. The methodology used was a mixed approach, quasi-experimental, bibliographical, with a descriptive, correlational, and explanatory level; the assessment instrument was the Bangsbo Sprint Test.